Effect of drying parameters on moisture content and papain enzyme activity of dried papaya - Zaki, Nurul Asyikin (2005)

(untitled)
Due to the importance of minimizing thermal stresses over drying and maintenance of relevant compounds, selection of proper drying condition is necessary to maintain the quality of the processed fruit. The aim of this project is to study the effect of drying parameters i.e. temperature, air velocity and geometry on moisture content and papain enzyme activity of dried papaya. Slices (0.5 x 1.5 x 1.5 cm) and cubes (1.0 cm3) of papaya were treated in tray drier at temperature (40, 50 and 60 Â°C) and air velocity (0.5, 1.0 and 1.5 m/s). Temperature was found to be significantly influencing the drying performance and quality retention for both slices and cubes. However, geometry was the most significant factor played as a controlling effect on moisture content, in which larger surface exposure helps temperature to take action strongly. Slices suffered higher water loss and enzyme degradation compared to cubes of papaya. Models obtained for moisture content and enzyme activity through response surface methodology were significant with R2 =0.93 and 0.80 respectively.